2014
DOI: 10.5005/jp-journals-10024-1549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Double Coating of One-step Self-etching Adhesive on Micromorphology and Microtensile Bond Strength to Sound vs Demineralized Dentin

Abstract: Aim The purpose of the present study was to evaluate (1) the one-step adhesive system application method (doubling the adhesive coatings) in regard to microtensile bond strength (MTB) and (2) the interfacial morphology of one-step adhesives to sound vs demineralized dentin. Materials and methods Forty dentin fragments were randomly allocated to 2 groups: D. demineralized dentin and S. sound dentin. Specimens were also subdivided into 2 groups (n = 10), according to the one-step adhesive [AEO (Adper Easy One)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…A total of 106 potentially relevant studies accessed the full-text evaluation phase. From these, 19 were excluded because there was no access to the full-text manuscript [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], resulting in a final number of 87 publications included for further qualitative assessment (Figure 1). After a full-text review, 9 articles were excluded because the bond strength was not tested [46][47][48][49][50][51][52][53][54], leaving 78 publications for qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 106 potentially relevant studies accessed the full-text evaluation phase. From these, 19 were excluded because there was no access to the full-text manuscript [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], resulting in a final number of 87 publications included for further qualitative assessment (Figure 1). After a full-text review, 9 articles were excluded because the bond strength was not tested [46][47][48][49][50][51][52][53][54], leaving 78 publications for qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the application of a hydrophobic resin coating may improve the degree of conversion in resin-dentin interfaces formed with either the self-etch or the etch-and-rinse bonding strategies (97). Similarly, Oliveira et al (96) demonstrated that application of double coats of the adhesive resin (one-step self-etch adhesive) produced longer resin tags than a single coat, at both sound and demineralized dentin; moreover, hydrolysis was probably lesser in the former situation, thus resulting in improved resin-dentin bonds.…”
Section: Modification Of the Bonding Protocolmentioning
confidence: 97%